2016
DOI: 10.1159/000445706
|View full text |Cite
|
Sign up to set email alerts
|

Acquired FVIII and FIX Inhibitors after Pregnancy: A Case Report

Abstract: Acquired hemophilia is a relatively rare clinical presentation, and most cases present with acquired FVIII inhibitor. The co-occurrence of inhibitors to multiple coagulation factors is uncommon. These autoantibodies may induce spontaneous life-threatening bleeding in patients who have had no previous bleeding disorder. Herein, we present a patient with postpartum acquired FVIII and FIX inhibitors who developed intramuscular hematoma and hemothorax during follow-up. She was then treated with activated prothromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The diagnostic parameter of AHA is the coagulation profile indicating a defect in the intrinsic pathway and, as mentioned before, the hallmark is an isolated deranged aPTT. A study by Kose et al [7] has reported a case of postpartum AHA with an initial aPTT value of >120 seconds, which is the highest to be reported yet. Our case presented with an aPTT value of 90 seconds, which raised the suspicion of acquired hemophilia, which we confirmed by mixing studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The diagnostic parameter of AHA is the coagulation profile indicating a defect in the intrinsic pathway and, as mentioned before, the hallmark is an isolated deranged aPTT. A study by Kose et al [7] has reported a case of postpartum AHA with an initial aPTT value of >120 seconds, which is the highest to be reported yet. Our case presented with an aPTT value of 90 seconds, which raised the suspicion of acquired hemophilia, which we confirmed by mixing studies.…”
Section: Discussionmentioning
confidence: 87%
“…Pregnancy-associated AHA represents 7-11% of the entire disease burden, with patients commonly presenting within one to four months of delivery with variable presentations of bleeding [1]. A review of the last 10 years of reported postpartum AHA cases showed that the ages of patients ranged between 19 years [7] to 40 years [8]. This indicates that AHA related to pregnancy can occur in any woman of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent bleeding events were obstetrical (43.3%), cutaneous (41.3% of reported cases), intramuscular (36.7%), and haemarthrosis (8%). Unusual sites were also reported, such as macrohaematuria ( n = 9), 23,31 haemothorax ( n = 2), 32,33 haematemesis ( n = 1), 16 prolonged bleeding after a venous or arterial puncture (3) 28,34,35 or dental procedure ( n = 6), 6,23,36 and a haemorrhagic corpus luteum ( n = 1) 37 . In 44 cases (29.3%), more than one type of bleeding occurred simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…AHA-related hemorrhages are associated with high morbidity and mortality [3][4][5], and risk of bleeding persists in the presence of inhibitors. An underlying cause is detected in approximately 50% of cases including autoimmune diseases, malignancy, infections, postpartum complication and others [6][7][8][9][10]. The FVIII: C and the inhibitor titer could not be measured in many hospitals due to the limited facility and resources, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%